MENINGKATKAN KEMAMPUAN BAHASA MELALUI METODE BERCERITA BERBASIS KEARIFAN LOKAL PADA ANAK KELOMPOK B2 - ayu surya; Serafina; Putu Indah Lestari (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
A young child is an individual who is unique and has characteristics according to the stages of their age. Language skills are one of the abilities of children who often experience obstacles in their development. The storytelling method based on local wisdom is a solution to improve early childhood language skills. This Classroom Action Research aims to determine the improvement of language skills through storytelling methods based on local wisdom in children of Group B2 PAUD Pelita Kasih. The research used a four-stage procedure, namely: action planning, action implementation, observation, and reflection, in two successive cycles with each cycle lasting for 3 days. Data collection methods used are observation, interviews, and documentation. The data analysis method used was descriptive analysis. The results showed an increase in the percentage of completeness that occurred in the initial observation until Cycle II. The rate of fullness in the initial observation of language skills was 6 children (35.29%), in Cycle I it reached 11 children (64.71%), and in Cycle II it reached 15 children (88, 24%). The conclusion of this research is that the implementation of the storytelling method based on local wisdom can improve the language skills of the children of Group B2 PAUD Pelita Kasih